Analysis of the thermodynamic performance of transcritical CO2 power cycle configurations for low grade waste heat recovery. (November 2022) - Wolf, Veronika; Bertrand, Alexandre; Leyer, Stephan
Abstract: Organic Rankine cycles employing carbon dioxide (CO2 ) for waste heat recovery became popular in the last years thanks to its excellent heat transfer characteristics and small environmental footprint. Low-grade waste heat (<240 °C) represents the major portion of excess heat globally, but it is hard to recover due to the small temperature gap of heat source and heat sink leading to a poor efficiency of the Rankine cycle. Therefore, numerous modifications of the power cycle layout were proposed by academia and industry — reheated expansion, recuperation and intercooled compression among them. This work compares ten cycle architectures for a defined waste heat source (60–100 °C) and heat sink (20 °C). Firstly, CO2 cycle architectures from literature are examined with its original operational parameters. Secondly, the predefined low-grade heat source is implemented into the cycle. The cycles are assessed regarding efficiency, mass flow and pressure. Results show that for source temperatures higher than 80 °C, recuperation and reheated expansion enhance the cycle performance whereas intercooled compression negatively affects the efficiency. The conventional configuration operated most efficiently for temperatures until 80 °C. A road map of thermodynamic efficiencies of CO2 cycle architectures for low-grade waste heat recovery up to 100 °C is delivered. Graphical abstract: Highlights: Analysis of 10 cycle configurations for low temperature waste heat recovery. A recuperator step and reheated expansion pay off already for low temperatures. Split flow configuration and intercooled compression affect the efficiency negatively. Thermodynamic cycle efficiencies in the range of 2.7 and 8.2 percentage points.